Desafios para implementação do policiamento comunitário - Kretschmer, Teilor (2024)
This work deals with the reorganization of the Military Police in accordance with today's society and the adaptation challenges faced by the corporation and by civilians themselves in the implementation of community policing, its methodology, action plans, strategies, highlighting the difficulties and barriers which prevent immediate installation in communities in Brazil. Showing that the growing social concern with the exponential increase in crime, and the creativity with which these crimes are being committed, where the police are always one step behind the criminal element, there is a solution, with a police united with the people. Gradually showing that this proposal works and that it is worth confronting the barriers imposed both by the community and by policing institutions, to put this project into operation, so innovative and functional, moving towards the policing of the future, much more preventive than repressive as in today's scenario.